2011
DOI: 10.1089/met.2011.0028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome Components in a Population of Bank Employees from St. Petersburg, Russia

Abstract: Metabolic syndrome and its distinct components were very prevalent in Russian bank office workers. AO was most prevalent component for females with metabolic syndrome, whereas HTN was most prevalent for males. Coexistence of HTN and AO was the most frequent coupling of metabolic syndrome components. Unhealthy lifestyle characterized the selected group and was associated with metabolic syndrome, especially low physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
6
23
2
4
Order By: Relevance
“…Recent investigation of 1,561 bank employees in Russia, St. Petersburg revealed that MS frequency in studied population is 21.5% according to IDF criteria and 18.8%, according to ATP2005 [9]. These data are corresponding well to the prevalence of MS in USA and Western Europe [4,5].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Recent investigation of 1,561 bank employees in Russia, St. Petersburg revealed that MS frequency in studied population is 21.5% according to IDF criteria and 18.8%, according to ATP2005 [9]. These data are corresponding well to the prevalence of MS in USA and Western Europe [4,5].…”
Section: Introductionsupporting
confidence: 61%
“…Controls were obtained from bank employee's cohort, which included 1,561 subjects [9]. As described, all subjects had been examined for the same anthropometrical parameters as in schizophrenia group, and at the fasting state in the morning their venous blood was drawn.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings were revealed in other studies in bank employees. 7,19,20,[25][26][27] However it was similar among males and females in the study by Ismail et al…”
Section: Table 4: Prevalence Of Hypertension In Bank Employees From Vmentioning
confidence: 86%
“…33 We also found that lack of physical activity was associated with MSx, which was consistent with findings of several previous studies. 23,34 Workers with MSx were less likely to consume fruits. Eating breakfast and interest in fatty food were not significantly different between studied workers with and without MSx.…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers reported that MSx was more common in men. 10,22,23 However, some studies reported a higher prevalence in women. 24,25 We found that workers with MSx had a higher mean age than those without.…”
Section: Discussionmentioning
confidence: 99%